Epistatic interactions between at least three loci determine the "rat-tail" phenotype in cattle. Issue 1 (December 2016) - Knaust, Jacqueline; Hadlich, Frieder; Weikard, Rosemarie; Kuehn, Christa
Abstract Background The "rat-tail" syndrome (RTS) is an inherited hypotrichosis in cattle, which is exclusively expressed in diluted coloured hair. The affected animals also suffer from disturbed thermoregulation, which impairs their health and growth performance. Phenotypic features that are similar to RTS are observed in dogs with black hair follicle dysplasia. Results We used a resource cross population between German Holstein and Charolais cattle breeds to prove that epistatic interactions between at least three independent genetic loci are required for the expression of the RTS phenotype. In this population, the RTS is exclusively expressed in animals with a eumelanic background that is due to the dominantE D allele at themelanocortin 1 receptor gene located onBos taurus autosome (BTA) 18. In addition, only the individuals that are heterozygous at thedilution locus on BTA5 that corresponds to thepremelanosome protein orsilver gene variantc.64G >A were classified as displaying a RTS phenotype. Linkage and whole-genome association analyses using different models and different pedigrees allowed us to map a third locus (hereafter referred to as theRTS locus) that is essential for the expression of the RTS phenotype to the chromosomal region between 14 and 22 Mb on BTA5. Our findings clearly demonstrate that theRTS anddilution loci are distinct loci on BTA5. Conclusions Our study provides evidence that theRTS locus has effects on hair conformation and coat colour dilution and that the effect on coat colour dilution is clearly independent from that of thedilution locus. Finally, our results excluded several other loci that were previously reported to be associated with or to underlie hair conformation or pigmentation traits as the causal mutations of RTS and also several major functional candidate genes that are associated with hypotrichosis in humans. Our finding on the identification of a three-locus interaction that underlies RTS provides a prime example of epistatic interaction between several independent loci that is required for the expression of a distinct phenotype.